Public policy and USM: an approach to fit a renewed sense of public purpose / James Campbell - Campbell, James (2010)
Malaysian Higher educational reform is an important and central aspect of the broader Malaysian public policy focus on excellence, development and national growth. This proposed paper intends to discuss analyze and critique the APEX program for Malaysian Universities. In particular the paper will investigate and discuss the way Universiti Sains Malaysia has interpreted and developed its strategic goals in light of its award of APEX status. Specifically I intend to discuss the strengths and limitations of the Universiti Sains Malaysia agenda, and contextualize it within a broader discussion about the directions of Malaysian Higher Education, in conditions of globalization, network society, and the knowledge economy. The challenges faced by the reform agenda at USM are significant and it is important that any understanding of the USM agenda be informed by deep reflection on the underlying philosophical aims and justifications for its direction. In this way my paper will attempt to show how the USM project is both an important part of Malaysian national development and a critical response to contemporary globalization, while at the same time an innovative and challenging intervention into public policy debate in Higher Education. The values and objectives of USM in regards to its strategic reorientation have implications far beyond the Higher Education sector and these implications will also be discussed.